Surgical interventions for high‐grade vulval intraepithelial neoplasia - Kaushik, Sonali (Cochrane Database Syst Rev, 2014)
BACKGROUND: This is an updated version of an original Cochrane review published in The Cochrane Library, 2011, Issue 1. Vulval intraepithelial neoplasia (VIN) is a pre‐malignant condition of the vulval skin. This uncommon chronic skin condition of the vulva is associated with a high risk of recurrence and the potential to progress to vulval cancer. The condition is complicated by its multicentric and multifocal nature. The incidence of this condition appears to be rising, particularly in the younger age group. There is a lack of consensus on the optimal surgical treatment method. However, the rationale for the surgical treatment of VIN has been to treat the symptoms and exclude any underlying malignancy, with the continued aim of preserving the vulval anatomy and function. Repeated treatments affect local cosmesis and cause psychosexual morbidity, thus impacting the individual's quality of life. OBJECTIVES: To evaluate the effectiveness and safety of surgical interventions in women with high‐grade VIN. SEARCH METHODS: We searched the Cochrane Gynaecological Cancer Group Trials Register and the Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE and EMBASE up to 1 September 2015. We also searched registers of clinical trials, abstracts of scientific meetings and reference lists of included studies, and contacted experts in the field. SELECTION CRITERIA: Randomised controlled trials (RCTs) that compared surgical interventions in adult women diagnosed with high‐grade VIN. DATA COLLECTION AND ANALYSIS: Two review authors independently abstracted data and assessed risk of bias. MAIN RESULTS: We identified one RCT, including 30 women, that met our inclusion criteria; this trial reported data on carbon dioxide (CO(2)) laser surgery versus cavitational ultrasonic surgical aspiration (CUSA). There were no differences in the risks of disease recurrence after one year of follow‐up, pain, scarring, dysuria or burning, adhesions, infection, abnormal discharge or eschar between women who underwent CO(2) laser surgery and those who received CUSA. The trial lacked statistical power, due to the small number of women in each group and the low number of observed events, but was at low risk of bias. AUTHORS' CONCLUSIONS: The included trial lacked statistical power, due to the small number of women in each group and the low number of observed events. The absence of reliable evidence regarding the effectiveness and safety of the two surgical techniques for the management of VIN therefore precludes any definitive guidance or recommendations for clinical practice.